Usuń niewymierność z mianownika.
a) 3/√2 - 1

b) 4 + √5/4 - √5

c) 2/2√3 - 4

d) 2 + √6/√6 - √3

e) 1 - √3/√7 + √3

f) a/a - √3; a ≠ √3

g) b + 1/b + √2; b ≠ -√2

h) b + 4/b - √3; b ≠ √3

i) a - 5/a - √5; a ≠ √5

j) a - 2/a + √2; a ≠ -√2

PILNE NA ZARAZ!

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T22:13:37+01:00
B]](4+√5):(4-√5)=(16+8√5+5):16-5=21+8√5/11
a]3:(√2-1)=3(√2+1):(1)=3√2+3
c]2:(2√3-4)=2(2√3+4):(12-16)=(4√3+8):-4=-√3-2
d](*2+√6):(√6-√3)=(2√6+2√3+6+3√2)/3
e]
(1-√3):(√7+√3)=(√7-√21-√3+3)/4
f]
a:(a-√3=a²+a√3/a²-3
g](b+1):(b+√2)=b²-b-b√2-√2/b²-2
h](b-4):(b-√3)=b²+b√3+4b+4√3/b²-3
i](a-5):(a-√5)=a²-5a+a√5-5√5/a²-5
j](a-2):(a+√2)=a²-2a+a√2-2√2/a²-2
2010-03-08T22:26:23+01:00
A) 3/√2 - 1 /*√2 +1
3√2+1/2-1

b) 4 + √5/4 - √5 /*4+√5
16+8√5+5/16-5=21+8√5/11

c) 2/2√3 - 4 /*2√3+4
4√3+8/12-16=4√3+8/-4= - √3+2

d) 2 + √6/√6 - √3 /*√6+√3
2√6+2√3+6+√18/6-3

e) 1 - √3/√7 + √3 /*√7-√3
√7-√3-√21+3/7-3

f) a/a - √3 /*a+√3 a ≠ √3 i-√3
a²+a√3/a²-3

g) b + 1/b + √2 /*b-√2 ; b ≠ -√2i √2
b²-b√2+b-√2/b²-2

h) b + 4/b - √3 /*b+√3 ; b ≠ √3 i -√3
b²+b√3+4b+4√3/b²-3

i) a - 5/a - √5 /*a+√5; a ≠ √5 i-√5
a²+a√5-5a-5√5/a²-5

j) a - 2/a + √2 /*a-√2 a ≠ -√2 i√2
a²-a√2-2a+2√2/a²-2
1 5 1
2010-03-08T23:35:28+01:00
A) 3/√2 - 1 |×(√2 +1)
3√2+1/2-1
b) 4 + √5/4 - √5 |×(4+√5)
16+8√5+5/16-5=21+8√5/11
c) 2/2√3 - 4 |×(2√3+4)
4√3+8/12-16=4√3+8/-4= - √3+2
d) 2 + √6/√6 - √3 |×(√6+√3)
2√6+2√3+6+√18/6-3
e) 1 - √3/√7 + √3 |×(√7-√3)
√7-√3-√21+3/7-3
f) a/a - √3 |×(a+√3)
a²+a√3/a²-3
g) b + 1/b + √2 |×(b-√2)
b²-b√2+b-√2/b²-2
h) b + 4/b - √3 |×(b+√3)
b²+b√3+4b+4√3/b²-3
i) a - 5/a - √5 |×(a+√5)
a²+a√5-5a-5√5/a²-5
j) a - 2/a + √2 |×(a-√2)
a²-a√2-2a+2√2/a²-2